"God, Have Mercy on Me, a Sinner": Vermeer and Bach on Soteriological Doubt - Proietta, Michael; Shipp, Caitlyn (Lumen et Vita, 2023)
This paper examines the question of soteriological doubt within the movement of faith, as aesthetically represented by Johannes Vermeer’s painting The Allegory of Faith and Johann Sebastian Bach’s Lutheran cantata Mein Herze schwimmt im Blut (BWV 199). In placing these two artistic works in dialogue with each other, we will articulate the triangulating movement between the soul, faith, and the crucified Christ within the wider circulating movement of salvific action. Therefore, this paper is divided into three sections: 1.) the acknowledgement of sin, subsequent remorse, and utter soteriological doubt, expressed by Vermeer’s representation of original sin and spiritual despair and by Bach’s expression of the emotional weight of sin and guilt; 2.) the triangulation in the middle of Vermeer’s painting and the circulation in the middle of Bach’s cantata; 3.) the destruction of sin and the consoling hope in personal salvation, expressed by Vermeer’s depiction of Christ’s triumph over sin and by Bach’s depiction of the soul’s elation and ultimate reconciliation with God. Finally, we will conclude by mapping these three sections in the movement of faith onto the three spiritual stages of purification, illumination, and union as described in the Christian mystical tradition.